Structure and Laboratory Diagnostics of Non-medical Consumption of Modern Synthetic Drugs - O. L. Balabanova; V. V. Shilov; A. N. Lodyagin; S. I. Glushkov (Неотложная медицинская помощь)
The emergence of new synthetic narcotic drugs is noted all over the world. The situation causes significant difficulties for toxicologists, resuscitators, narcologists, and clinical laboratory diagnostics doctors due to the lack of available data on the clinical picture of poisoning by these compounds and laboratory diagnostic methods. In most cases, the clinical picture of drug intoxication or poisoning with new synthetic substances differs from the symptoms caused by previously known drugs, such as cocaine or opiates. Therefore, chemical toxicological research is one of the important aspects for establishing the fact of intoxication or poisoning.